'Fuller's Internal Morality of Law'. Issue 9 (September 2016) - Rundle, Kristen
Abstract: Teased out through a playful tale about a king who failed in eight ways to make law, Lon L. Fuller's eight principles of the 'internal morality of law' became an important contribution to legal philosophy and rule of law theory alike. Moreover, it was Fuller's claim that his principles were not just internal to the enterprise of law, but also 'moral' in character, that precipitated a particular kind of 'natural law versus legal positivism' contest that continues among legal philosophers today. But as a recent revival of interest in Fuller's thought indicates, his scholarly agenda around the idea of 'the internal morality of law' was wider still and deserves revisiting for the range of avenues of inquiry it opens up.